The benefits and harms of surveying adolescents about intimate partner violence and verbal, physical and sexual abuse by Tracy McClinton Appollis. - McClinton Appollis Tracy (Centre for Public Mental Health, 2014)
Includes abstract. Includes bibliographical references.